Development and validation of a self-control scale from an Islamic perspective - Aissa, Ahmed Hamdi (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Self-control in western psychology is in one way or the other different from the Islamic concept of it. Unlike western studies on self-control, there are no scientific and empirical studies being done on the Islamic perspective of self-control yet even though it is widely applicable in the life of Muslims. The aim of this study is to develop an instrument that measures self-control from an Islamic perspective. The instrument will open doors for more studies on the Islamic perspective of self-control to be conducted. For this to happen, the instrument had to undergo two main stages in the preliminary level. In the first stage, the instrument was given to subject matter experts to assess and review. In the second stage, after necessary corrections had been made, it was administered to a sample of 201 male and female students from four faculties in the International Islamic University Malaysia. The data collected was analyzed using exploratory factor analysis (EFA). The findings of the first stage indicated that the instrument was not ready and had to go through substantial changes in terms of item construction. The modified version of the instrument achieved good satisfactory results from subject matter experts who stated that the instrument has achieved good content validity. The findings of the second stage indicated that there were only 19 items which remained valid after the EFA process which made up four factors instead of the 11 in the first version, namely; avoiding Islamically unacceptable enjoyment, strong Islamic faith, practice of Islamic teachings, and striving (mujÉhadah). The refined instrument was then found to have a Cronbach's alpha of .908 from the results of the pilot study. The result also showed constructs loadings greater than .40 and correlations lower than .90 which served as an evidence of having good convergent and divergent validity. Lastly, the instrument showed good reliability as its factors' loadings were all greater than .60.